Self-Reported COVID-19 Vaccine Status and Barriers for Pediatric Emergency Patients and Caregivers - Amanda M. Szarzanowicz; Kendra Fabian; Maya Alexandri; Carly A. Robinson; Sonia Singh; Michael Wallace; Michelle D. Penque; Nan Nan; Changxing Ma; Bradford Z. Reynolds; Bethany W. Harvey; Heidi Suffoletto; et al. (Western Journal of Emergency Medicine)
Objective: This study determined if the caregivers of children in the emergency department (ED) have the same COVID-19 vaccination status as the child, the reasons they chose to not vaccinate the child, and self-identified barriers to vaccination to determine if the ED is appropriate for vaccination intervention. Methods: A survey was administered to caregivers of pediatric ED patients at four Children’s Hospitals in: Augusta, GA, Buffalo, NY, Madison, WI, and Sacramento, CA. Participants were asked about their and the child’s demographics, vaccination status, and barriers to vaccination. We used descriptive statistics, Cohen's kappa, and logistic regression to analyze responses. Results: 941 caregivers were considered for enrollment, and 800 consented to participation. Participants were 75% women with a mean age of 40.9 ± 8.9 years. 51% (409) of the pediatric ED patients were COVID-19 vaccinated, as were 74% (591) of the caregivers. There was variation across sites, but overall, 15% of caregivers of unvaccinated children wanted the child tobe vaccinated with the most common barriers to vaccination identified as safety data (25%), time availability (20%), and ability to obtain an appointment (13%). The most common reason for not wanting the child COVID-19 vaccinated was concern the vaccine didn’t work or had too many side effects. Conclusion: A small but clinically important group of pediatric ED patients are not COVID-19 vaccinated but their caregivers want them to be vaccinated, indicating that consideration should be given to offering vaccination in the ED. Reasons for avoiding COVID-19 vaccination were primarily concerns with efficacy and side effects.